Propuesta arquitectonica para un centro de investigación y producción piscicola Gigante - Huila (2020)
The Research presented below addresses the issue of fish farming in Huila and its opportunities for growth in respect to the economy, their processes, needs and opportunities that this issue brings to the emergence of a department or a municipality, giving all points of argumentative views with their theoretical concepts, legal concepts and historical concepts about thematic All of this from some problems and opportunities identified in the department in front of the infrastructure and research shortages and the fish farm demand that´s being presented in the last years in Colombia. Positioning the Huila as the biggest producer thanks to the Betania reservoirs and the quimbo created in the department. Issues of environmental impacts are addressed, and how pollution and effluents can contaminate a municipality or an entire department